TNF-α and CD8+ T cells mediate the beneficial effects of nitric oxide synthase-2 deficiency in pulmonary paracoccidioidomycosis. - Simone Bernardino; Adriana Pina; Maíra Felonato; Tânia A Costa; Eliseu Frank de Araújo; Cláudia Feriotti; Silvia Boschi Bazan; Alexandre C Keller; Katia R M Leite; Vera L G Calich (Public Library of Science (PLoS), 2013)
Background Nitric oxide (NO), a key antimicrobial molecule, was previously shown to exert a dual role in paracoccidioidomycosis, an endemic fungal infection in Latin America. In the intravenous and peritoneal models of infection, NO production was associated with efficient fungal clearance but also with non-organized granulomatous lesions. Because paracoccidioidomycosis is a pulmonary infection, we aimed to characterize the role of NO in a pulmonary model of infection. Methodology/principal findings C57Bl/6 wild type (WT) and iNOS(-/-) mice were i.t. infected with 1×10(6) Paracoccidioides brasiliensis yeasts and studied at several post-infection periods. Unexpectedly, at week 2 of infection, iNOS(-/-) mice showed decreased pulmonary fungal burdens associated with an M2-like macrophage profile, which expressed high levels of TGF-β impaired ability of ingesting fungal cells. This early decreased fungal loads were concomitant with increased DTH reactions, enhanced TNF-α synthesis and intense migration of activated macrophages, CD4(+) and CD8(+) T cells into the lungs. By week 10, iNOS(-/-) mice showed increased fungal burdens circumscribed, however, by compact granulomas containing elevated numbers of activated CD4(+) T cells. Importantly, the enhanced immunological reactivity of iNOS(-/-) mice resulted in decreased mortality rates. In both mouse strains, depletion of TNF-α led to non-organized lesions and excessive influx of inflammatory cells into the lungs, but only the iNOS(-/-) mice showed increased mortality rates. In addition, depletion of CD8(+) cells abolished the increased migration of inflammatory cells and decreased the number of TNF-α and IFN-γ CD4(+) and CD8(+) T cells into the lungs of iNOS(-/-) mice. Conclusions/significance Our study demonstrated that NO plays a deleterious role in pulmonary paracoccidioidomycosis due to its suppressive action on TNF-α production, T cell immunity and organization of lesions resulting in precocious mortality of mice. It was also revealed that uncontrolled fungal growth can be overcome by an efficient immune response.